Law and Lawbooks in Mediaeval Wales - Chapman Stacey, Robin (History compass, 2010)
Together with the Welsh language, mediaeval Welsh law has long been regarded as critical to Welsh national identity. The ongoing significance of the ‘law of Hywel’, together with the traditionally philological orientation of Celtic Studies as a discipline, have shaped the questions scholars have put to the laws over the past several decades. This article traces the manner in which the field has evolved, from an interest in Common Celtic institutions and comparisons with early Ireland, to the more contemporary emphasis on the Welsh lawbooks as part of the European-wide resurgence of law in the 12th and 13th centuries. It suggests that the way forward lies both in providing modern editions of texts not yet accessible, and in incorporating new theoretical perspectives now being put to use in other legal history fields into the study of the laws.